2013
DOI: 10.1021/cs400159w
|View full text |Cite
|
Sign up to set email alerts
|

Ceria-Doped Ni/SBA-16 Catalysts for Dry Reforming of Methane

Abstract: Ni-ceria nanoparticles (Ni/Ce = 1/1) in the cage-like pores of SBA-16 were prepared and evaluated in methane dry reforming reactions. Coexistence of ceria in NiCe/SBA-16 resulted in forming uniformly sized Ni particles (av. 5.7 nm) within the mesopores of SBA-16, because of the confinement effect from the framework of SBA-16 and the strong interaction between Ni and ceria. Ceria addition facilitated the reduction of NiCe/SBA-16 compared with Ni/SBA-16, and Ce3+ was the dominant species in both fresh and used N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
200
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(206 citation statements)
references
References 79 publications
6
200
0
Order By: Relevance
“…Such destruction can take place under the preparation procedure used in this study, but the TEM images (Fig. 4(a)) prove that SBA-16 framework and pore structures remained intact, similar to the study done on DRM in [12].…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Such destruction can take place under the preparation procedure used in this study, but the TEM images (Fig. 4(a)) prove that SBA-16 framework and pore structures remained intact, similar to the study done on DRM in [12].…”
Section: Resultssupporting
confidence: 81%
“…From the three types of carbon discussed earlier, Cα is a reactive intermediate that does not have influence on catalyst stability; Cβ represents nanotubes and Cγ, a graphitic carbon, which is the most detrimental type responsible of catalyst deactivation [20,28,29]. Fig.…”
Section: Physicochemical Properties Of the Spent Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…A suggested solution to inhibit carbon deposition is to promote the catalyst with a metal oxide, especially CeO 2 . The latter is characterized by redox properties (Ce 4+ ↔ Ce 3+ ) that promote oxygen vacancies formation, thus enhancing the mobility of surface oxygen whose presence contributes in lowering carbon deposition on the metallic particles [4][5][6][7]. It was also reported that both metal dispersion and metal-support interaction are improved in presence of CeO 2 [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…Cerium(IV) oxide (ceria) and metal-doped ceria nanoparticles have been developed for their role in catalysis [30][31][32][33][34][35][36]. One of the features that makes ceria attractive for catalysis is its ability to release/uptake oxygen from its lattice without losing its structural integrity [37].…”
Section: Introductionmentioning
confidence: 99%